2002
DOI: 10.1007/bf02898059
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-topoisomerase I autoantibody in patients with silicosis

Abstract: Objectives: The aim of this study was to detect anti-topoisomerase l (anti-topo I) autoantibodies, which are known to be limited in systemic sclerosis patients, in silicosis patients with no clinical symptoms of autoimmune disease.Methods: Serum anti-topo I autoantibodies were detected using ELISA. Differences in clinical parameters between patients with and without anti-topo I autoantibodies were analyzed.Results: Seven of 69 patients had anti-topo I autoantibodies. These 7 patients showed elevated PaCO 2 val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In addition, silicosis patients without bullous diseases tested positive for anti-desmoglein autoantibodies and the frequencies of HLA-DRB1*04, HLA-DQB1*03, *0303, and *05, and HLA-DPB1*0402 and *0501 alleles were higher in these patients than in a healthy Japanese control population in the literature [29,30]. Moreover, the relationship between the autoantibodies in silicosis patients and HLA phenotypes was also analyzed in silicosis patients with anti-topoisomerase I autoantibodies [30][31][32][33][34], and the results obtained revealed that the allelic frequency of HLA-DQB1*0402 was significantly higher in anti-topoisomerase I positive Japanese silicosis patients than in anti-topoisomerase I negative patients or healthy donors [30][31][32][33][34].…”
Section: Autoantibodies Detected In Silicosis Patients and Their Relamentioning
confidence: 99%
“…In addition, silicosis patients without bullous diseases tested positive for anti-desmoglein autoantibodies and the frequencies of HLA-DRB1*04, HLA-DQB1*03, *0303, and *05, and HLA-DPB1*0402 and *0501 alleles were higher in these patients than in a healthy Japanese control population in the literature [29,30]. Moreover, the relationship between the autoantibodies in silicosis patients and HLA phenotypes was also analyzed in silicosis patients with anti-topoisomerase I autoantibodies [30][31][32][33][34], and the results obtained revealed that the allelic frequency of HLA-DQB1*0402 was significantly higher in anti-topoisomerase I positive Japanese silicosis patients than in anti-topoisomerase I negative patients or healthy donors [30][31][32][33][34].…”
Section: Autoantibodies Detected In Silicosis Patients and Their Relamentioning
confidence: 99%
“…2b) [45], a certain fraction of helper T cells in SIL is thought to survive longer with prolonged activation [45]. On the other hand, among the various auto-antibodies, we found in SIL serum [46][47][48][49][50], we detected a functional anti-Fas autoantibody (Fig. 2c) [50].…”
Section: Effects On Nk Cellsmentioning
confidence: 70%
“…1,2 Since autoantibodies against unknown antigens are present in the serum of these patients, their sera have been analysed for autoantibodies directed against the Fas molecule, and here we report the detection of anti-Fas autoantibodies. In previous studies, we found autoantibodies directed against DNA topoisomerase I, 3 desmogleins 4 and caspase-8. 5 The SPOTs system is a technology that allows the solidphase synthesis of an extensive series of short peptides for the systematic analysis of antibody epitopes.…”
Section: Introductionmentioning
confidence: 75%
“…Since autoantibodies against unknown antigens are present in the serum of these patients, their sera have been analysed for autoantibodies directed against the Fas molecule, and here we report the detection of anti‐Fas autoantibodies. In previous studies, we found autoantibodies directed against DNA topoisomerase I, 3 desmogleins 4 and caspase‐8 5 …”
Section: Introductionmentioning
confidence: 88%